PHARMACOECONOMICS AS A STRATEGY FOR OPTIMIZING THE COST-EFFECTIVENESS OF ANTIMICROBIAL AGENTS: A REVIEW - Furtado, Bruna Brasil Rodrigues (Seven Editora, 2025)
The hospital’s management is complex, requiring a broad and multidisciplinary set of managerial competencies, ranging from administration concepts and human resources to specific knowledge related to the various professionals and clients it serves. In the current context, antimicrobial resistance is a major public health issue, as its expansion threatens the use of antimicrobials, medications that account for over 30% of the therapeutic arsenal used in hospitals. This study aimed to conduct a literature review on the topic. The results of this review demonstrated the important role of pharmacists, who should be included in and actively participate in the hospital infection control committee to minimize the spread of bacterial resistance in the hospital environment by applying techniques for the rational use of these medications. DOI: 10.56238/sevened2025.018-051